Left ventricular dysfunction, natriuretic peptides, and mortality in an urban population. Issue 1 (1st July 2001) - McDonagh, T A; Cunningham, A D; Morrison, C E; McMurray, J J V; Ford, I; Morton, J J; Dargie, H J
Abstract : OBJECTIVE: To report the mortality of left ventricular systolic dysfunction (LVD), assessed objectively by echocardiography, and its association with natriuretic peptide hormones in a random sample of 1640 men and women aged 25–74 years from a geographical, urban population. METHODS: Left ventricular function was measured by echocardiography in 1640 attendees studied in 1992–3. LVD was defined as a left ventricular ejection fraction (LVEF) ⩽ 30%. Plasma concentrations of N-terminal atrial natriuretic peptide (N-ANP) and brain natriuretic peptide (BNP) were measured by standard radioimmunoassays. Mortality was documented at four years. RESULTS: The four year all cause mortality rate in the whole cohort was 4.9% (80 deaths). It was 21% (nine deaths) in those with an LVEF ⩽ 30% and 4% in those whose LVEF was > 30% (p < 0.001). The median (interquartile range) BNP concentration in those who died was 16.9 pg/ml (8.8–27) and 7.8 pg/ml (3.4–13) in survivors (p < 0.0001). Similarly, N-ANP had a median concentration of 2.35 ng/ml (1.32–3.36) in those with a fatal outcome and 1.27 ng/ml (0.9–2.0) in those alive at four years (p < 0.0001). Subjects with an LVEF ⩽ 40% also had a significant mortality rate of 17% if they also had a BNP concentration ⩾ 17.9 pg/ml compared with 6.8% if their BNP was below this concentration (p = 0.013). Multivariate analysis revealed the independent predictors of four year all cause mortality to be increasing age (p < 0.001), a BNP concentration ⩾ 17.9 pg/ml (p = 0.006), the presence of ischaemic heart disease (p = 0.03), and male sex (p = 0.04). CONCLUSIONS: LVD is associated with a considerable mortality rate in this population. BNP also independently predicts outcome. In addition to its role as a diagnostic aid in chronic heart failure and LVD, it provides prognostic information and clarifies the meaning of a given degree of LVD.